البناء النفسي في القرآن الكريم (Journal Of Educational and Psychological Researches, 2013)
This research psychological construction in the Koran, and the researcher with an overview of the importance of and the need HSCode Elbe.Built Koran souls on faith and piety , the more you build good was the commitment approach Koran evident , because the Koran built for these souls path will not Tdilh never astronomer can occur amendment or a change in the character of a man in his behavior it is necessary to modify or change his ideas and trends as the human behavior is influenced by a major impact his ideas and trends , the Inn Koran to change people's ideas and attitudes and behavior and to guide them and change what they are in it from going astray and ignorance and directing them to what it Slaham and well-being , and provide them with new ideas about the nature of man and his mission in life and the values ​​and ethics of new and ideals of life.That was the motivation for the selection of this research, which was entitled "The psychological construction in the Koran", then touched the researcher to the target year as the research aims to identify its psychological construction in the Koran, and to achieve the aim of the research dealt with the researcher Quran and Hadith books adopted, the approach Find a researcher has adopted a descriptive analytical method, and after it touched seeking psychological construction in the Koran and divided into four sections .Was the first of the Faith Behgadh uniformity, kpf its effect in the construction of self , because of faith in this dogma reassuring GOP Alengs , while the second was about faith and a sense of security because the faith to achieve security and stability , while the third was from the faith of belonging to the group , because the nature of self- love meeting this is because the insurer strong his brother , and comes section IV , who spoke it on the acts of worship that are the basis of the flowering of self , because in prayer and fasting , Hajj and Zakat of Reflections and Faaudhat back on self comfortable and at ease , either calculate the self and constant vigilance is through patience and remembrance of Allah Almighty, and repentance , asking for forgiveness and all of these stations to avail itself of which insured its fuel to be always with God and who is with God Almighty does not seep into his heart, anxiety and chaos.As for the construction of the objective was the same through the limits of self-knowledge and validation, and the rejection of patristic, and fairness and not people digest their rights, and all these signals must be stopped then the insured, in order to have a balanced personality to consider things carefully and objectively.Find out and many of the results, including:1- To each of the limits and capabilities, and knowledge of sending in the human soul kind of reassuring psychological, and calm the inevitable to restore balance to each behavior shall be disciplined under the limits of energy or Alusa, thus putting an end to what we see from recklessness or vanity and the accompanying recklessness leading to arrogance or arrogance, which is forbidden by God (Almighty) as a manifestation of God in the post some of his qualities, and this is what dignifying for a Muslim.2-The digestion of the rights of others, and spreading injustice, aggression, and other parameters of injustice, tyranny and arrogance and intransigence, and it all affects the community a sense of frustration and hinder the process of the progress of civilization and intellectual, and psychological, and the crash in the community that the ability to create and innovate and distract him from the method of God in succession. 3-The recognition of the master of evidence, as they say, and the ability of humans and the capacity is limited, however, counting do what you can jihad, whatsoever, and the penalty Institutes of paradise, and when mixes with fancy some aspects of the work of the Muslim, the so profound impact at the same insured astute, even if I feel that initiated the error correction, and quit, and those expressed by the Quran, repentance, and sincere manifestations of self-insured initiative immediately to cure this disease, to take off from repeating the error and regret it, turning the treatment into an effective weapon in self build strong fixed.4-That flexibility of mind linking life of the believer and his thinking in the bond close of reflection and contemplation, and continuous learning balanced that found the psychological comfort, but his behavior toward her, which continued learning no doubt that Islam urged him and ordered it, and that flexibility and that learning, which is about the Arab in Mecca, after his faith to another human being, rolled up all the pages of his painful past, and has been seen before, and above all to the values ​​of Islam while refusing to see it adheres strongly unmatched including Islam commanded him and called him.5-Faith makes the insured owner of a balanced personality profile that called for the Koran.6-Search and decides, is crucial to victory with faith, this does not mean non-introduction of the reasons, but trust in God with faith.7-Failure Jihad is not pleased by God (Almighty) for the impact of the disciple in the hearts of myself retarded First, Second, and in the hearts of leaders.